2010
DOI: 10.1111/j.1752-1688.2009.00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Satellite Rainfall Estimates Over South America – Possible Applicability to the Water Management of Large Watersheds1

Abstract: Pereira Filho, Augusto J., Richard E. Carbone, John E. Janowiak, Phillip Arkin, Robert Joyce, Ricardo Hallak, and Camila G.M. Ramos, 2010. Satellite Rainfall Estimates Over South America – Possible Applicability to the Water Management of Large Watersheds. Journal of the American Water Resources Association (JAWRA) 46(2):344‐360. DOI: 10.1111/j.1752‐1688.2009.00406.x Abstract:  This work analyzes high‐resolution precipitation data from satellite‐derived rainfall estimates over South America, especially over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 28 publications
2
50
0
1
Order By: Relevance
“…10). In line with previous work by Scheel et al (2011) andPereira Filho et al (2010), better performance was obtained for monthly timescales compared to the daily scale. Unexpected, however, was the fact that the annual scale resulted worse compared to the daily scale, in particular for CMORPH and PERSIANN-CCS-Adj, which was due to the amplification of small systematic biases at the daily timescale when aggregated into the annual one, passing from 2922 days to only 8 annual values.…”
Section: Which Sre Performs Best For Different Timescales?supporting
confidence: 78%
See 1 more Smart Citation
“…10). In line with previous work by Scheel et al (2011) andPereira Filho et al (2010), better performance was obtained for monthly timescales compared to the daily scale. Unexpected, however, was the fact that the annual scale resulted worse compared to the daily scale, in particular for CMORPH and PERSIANN-CCS-Adj, which was due to the amplification of small systematic biases at the daily timescale when aggregated into the annual one, passing from 2922 days to only 8 annual values.…”
Section: Which Sre Performs Best For Different Timescales?supporting
confidence: 78%
“…CMORPH has been reported to outperform other SRE products over the Australian tropics Joyce et al, 2004), central United States (Behrangi et al, 2011) and Europe (Kidd et al, 2012). As many SRE products that do not rely on rainfall gauge data, CMORPH tends to overestimate the amount of precipitation during wet periods (Behrangi et al, 2011). Pereira Filho et al (2010 compared CMORPH rainfall estimates over South America (Amazon Basin), at 8 km spatial resolution, with available rainfall observations at daily, monthly, and yearly timescales.…”
Section: Cmorphmentioning
confidence: 99%
“…This expresses increasing food demand, household and other development activities which require availability and access to water. For the problem to be dealt with, it is proposed to interchangeably use the lake and rainfall water [42,43]. Despite the fact that integrated water resources management action is being taken, it is still mandatory to consider climate change, global population growth and other increasing water Figure 5.…”
Section: Climate Change and Watermentioning
confidence: 99%
“…This expresses increasing food demand, household and other development activities which require availability and access to water. For the problem to be dealt with, it is proposed to interchangeably use the lake and rainfall water [42,43]. …”
Section: Climate Change and Watermentioning
confidence: 99%
“…A number of them showed that low intensities are overestimated and high intensities are underestimated in Africa [4,9,10], in United States [11,12], in South America [13,14] and in Asia [15][16][17][18]. In terms of seasonality, products are better in the rainy season [4,18,19] or in summer [20][21][22][23][24], when the precipitation is warm and convective. These comparisons based on the intensity and seasonality criteria have been widely studied, and the obtained results confirm the generalities previously validated by many authors.…”
Section: Introductionmentioning
confidence: 99%